Evaluating the Use of Glucocorticoids Among Belimumab‐Treated Patients With Systemic Lupus Erythematosus in Real‐World Settings Using the Rheumatology Informatics System for Effectiveness Registry. Issue 10 (24th July 2022) - Hammam, Nevin; Evans, Michael; Bell, Christopher F.; Gairy, Kerry; Yazdany, Jinoos; Schmajuk, Gabriela
Abstract : Objective: Glucocorticoids are part of standard therapy for systemic lupus erythematosus (SLE), despite adverse effects associated with long‐term treatment. Belimumab improved clinical manifestations of SLE and reduced glucocorticoid doses in clinical trials and clinical practice; however, associations have not been examined using multi‐institutional electronic health record (EHR) data. Using the Rheumatology Informatics System for Effectiveness registry, we examined glucocorticoid use patterns among belimumab‐treated adults with SLE. Methods: This retrospective analysis (GSK Study 209267) used EHR prescription records of patients with SLE managed by rheumatologists. Eligible patients had an index date (first belimumab prescription) between January 2014 and June 2018. The primary analysis compared patients' mean daily oral glucocorticoid (prednisone equivalent) dose over the 6 months preindex versus 6 months post index. An exploratory analysis assessed glucocorticoid doses at 12 and 24 months post index for patients with extended follow‐up. Results: Of the 1987 patients receiving their first belimumab prescription, 767 had available glucocorticoid prescribing data, whereas 204 (primary analysis population) had glucocorticoids prescribed in the 6 months preindex and received belimumab according to the prescribing information for the first 8 weeks post index. The mean (SD) glucocorticoid dose was 12.5 (13.5) mg/day 3 months preindex, reducing to 10.3 (10.6) mg/day over the 6 months post index, and 8.7 (9.4) and 9.0 (9.3) mg/day at 12 and 24 months post index. Conclusion: This study showed reductions in mean daily glucocorticoid dose after belimumab initiation. Several limitations of EHRs for real‐world effectiveness research were identified, which limited interpretation of results and may inform future study designs.